Digital medicines for adherence support: A conceptual framework and qualitative study of adherence among chronically ill patients. (11th November 2021) - Castillo, Anabel F; Davis, Alexander L; Fischhoff, Baruch; Krishnamurti, Tamar
Digital medicine programs (DMPs) are emerging technologies that use sensor-enabled medicine to detect when patients have taken their medication and then provide feedback about adherence. We use qualitative methods to understand how patients change their behavioral patterns while participating in a DMP intervention. An influence diagram outlining the factors hypothesized to affect adherence in DMPs constructed from prior scientific research and expert input was created. Subsequently, we conducted semi-structured interviews with 10 patients to see if their experience supported the relationships outlined in the model. We identified three pathways by which DMPs are likely to change behavior around medication adherence: (1) providing patients and providers with accurate, personalized information about adherence; (2) improving patient–provider interactions by structuring them around this information; and (3) facilitating routines and habits for medication use. Chronically ill patients often fail to adhere to drug regimens. Patients in a DMP intervention used the DMP-provided information to better understand drug efficacy and collaborated with their physician to develop adherence strategies. DMPs can promote medication adherence among patients who are willing to use them and may be most effective if physicians are active partners in the DMP.